Antaretylus humus n. gen., n. sp. from the Subantarctic (Nematoda: Tylenchoidea) - Sher, S. A. (Society of Nematologists, 1973)
Antarctylus humus n. gen., n. sp. from peat soil in the subantarctic is proposed. It can be distinguished from the most closely related genus Helicotylenchus by the arrangement of the esophageal glands, the broadly rounded lip region, and the tapering pointed tail in the female.